The Role of Some Special Stains in Evaluating Histological Changes in Bone Marrow in Childhood Acute Leukemia Patients with Some Blood Indicators - Taha, Yassin Alaa; Ayoub, Prof. Rasha Hamed (Journal of Science in Medicine and Life, 2024)
LeukemiaLeukemia is a malignant disorder of blood-forming stem cells characterized by abnormal proliferation of immature cells in the bone marrow and peripheral blood. Leukemia is classified into two types: Acute acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML). The aim of the study is to evaluate the histological changes in biopsies. Bone marrow in acute leukemia patients using basic dyes and some special dyes and evaluating some blood and physiological parameters. 30 samples were collected from pediatric patients diagnosed with acute leukemia by specialist doctors from Al-Tayeb City - Baghdad Teaching Hospital - Hematology Unit. Sample collection began from September 2023 to January 2024, and bone marrow swabs and biopsies were collected. The current study identified 7 pediatric patients with acute myeloid leukemia (AML), 2 males and 5 females. The number of pediatric patients with acute lymphoblastic leukemia (ALL) was 23 children, 11 males and 12 females, and their ages ranged between 1-13. One year. The comparison results indicated that there were significant differences for the variable (plts) between patients, while there were no significant differences for the other variables at the level ((p ≤ 0.05)). The study also showed that fever and pallor were the most common feature among patients. Other symptoms appeared in the patients. The most important of these are bleeding and general pain for both types AML and ALL, and bone marrow is of great importance in diagnosing patients with acute leukemia.